2015
DOI: 10.1016/s0140-6736(14)60921-1
|View full text |Cite
|
Sign up to set email alerts
|

ST-segment elevation myocardial infarction in China from 2001 to 2011 (the China PEACE-Retrospective Acute Myocardial Infarction Study): a retrospective analysis of hospital data

et al.

Abstract: Summary Background Despite the importance of ST-segment elevation myocardial infarction (STEMI) in China, no nationally representative studies have characterised the clinical profiles, management, and outcomes of this cardiac event during the past decade. We aimed to assess trends in characteristics, treatment, and outcomes for patients with STEMI in China between 2001 and 2011. Methods In a retrospective analysis of hospital records, we used a two-stage random sampling design to create a nationally represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
358
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 357 publications
(377 citation statements)
references
References 30 publications
13
358
5
1
Order By: Relevance
“…Identifying the determinants of IHM and PCI use among AMI patients is likely to be important in developing targeted interventions to improve access to PCI and to reduce AMI mortality 23. Previous studies, however, used data from a specific region or selected hospitals24, 25, 26, 27, 28 or focused on patients with ST‐segment–elevation myocardial infarction (STEMI) 29, 30, 31, 32, 33, 34. Given the marked geographic, economic, demographic, and cultural diversity in China, a nationwide investigation using representative samples is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the determinants of IHM and PCI use among AMI patients is likely to be important in developing targeted interventions to improve access to PCI and to reduce AMI mortality 23. Previous studies, however, used data from a specific region or selected hospitals24, 25, 26, 27, 28 or focused on patients with ST‐segment–elevation myocardial infarction (STEMI) 29, 30, 31, 32, 33, 34. Given the marked geographic, economic, demographic, and cultural diversity in China, a nationwide investigation using representative samples is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Although some patients received PCI within the effective time window after onset, there was no obvious decrease in the in-hospital mortality rate and major complications in AMI patients in China for the past 10 years. The in-hospital mortality rate was within 5-15% (2). Therefore, further investigations are warranted to optimize its therapeutic benefits for AMI and develop novel therapies to decrease the mortality rate of AMI.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the benefits of PCI, equal proportion of patients in 2011 received PCI and fibrinolysis, and it has been shown that urokinase, a drug for which there are little data demonstrating effectiveness in STEMI, is the preferred fibrinolytic agent in China 18. In addition to the possibility of suboptimal use of reperfusion, there may be other care processes that we did not measure in this analyses, such as the use of traditional Chinese medicines in 70% of STEMI patients,2 contributing to outcomes. Nonetheless, the relationship between hospitals' performance on process measures and risk‐standardized outcomes is known to be complex 19, 20.…”
Section: Discussionmentioning
confidence: 99%
“…Given that care for life‐threatening conditions, such as ST‐elevation myocardial infarction (STEMI), is provided by hospitals, understanding the performance of these organizations can inform quality improvement efforts. A handful of studies of Chinese patients have revealed gaps in the care provided to individual patients with acute coronary syndromes 1, 2. Although these studies have provided an important foundation for quality improvement efforts, patient‐level analyses pool data across hospitals, which means that variation in performance among individual institutions cannot be detected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation